TASK-3 Gene Knockdown Dampens Invasion and Migration and Promotes Apoptosis in KATO III and MKN-45 Human Gastric Adenocarcinoma Cell Lines - Cikutović-Molina, Rocio (Int J Mol Sci, 2019)
Incidence and mortality of gastric cancer is increasing worldwide, in part, because of the lack of new therapeutic targets to treat this disease. Different types of ion channels participate in the hallmarks of cancer. In this context, ion channels are known to exert control over the cell cycle, mechanisms that support survival, angiogenesis, migration, and cell invasion. In particular, TASK-3 (KCNK9), a member of the K2P potassium channel family, has attracted much interest because of its oncogenic properties. However, despite multiple lines of evidence linking TASK-3 to tumorigenesis in various types of cancer, its relationship with gastric cancer has not been fully examined. Therefore, we set out to assess the effect of TASK-3 gene knockdown on KATO III and MKN-45 human gastric adenocarcinoma cell lines by using a short hairpin RNA (shRNA)-mediated knockdown. Our results demonstrate that knocking down TASK-3 reduces cell proliferation and viability because of an increase in apoptosis without an apparent effect on cell cycle checkpoints. In addition, cell migration and invasion are reduced after knocking down TASK-3 in these cell lines. The present study highlights TASK-3 as a key protein involved in migration and cell survival in gastric cancer and corroborates its potential as a therapeutic target for gastric cancer treatment.